2008
DOI: 10.1634/stemcells.2007-0785
|View full text |Cite
|
Sign up to set email alerts
|

Statin and Stromal Cell-Derived Factor-1 Additively Promote Angiogenesis by Enhancement of Progenitor Cells Incorporation into New Vessels

Abstract: Angiogenesis requires the mobilization of progenitor cells from the bone marrow and homing of progenitor cells to ischemic tissue. Statins facilitate the former, and the chemokine stromal cell-derived factor-1 (SDF-1) enhances the latter. Their combined influence on angiogenesis was studied in vivo in the ischemic hindlimb C57BL/6 mouse model. The ischemic to non-ischemic perfusion ratio increased from 0.29 ؎ 0.02 immediately after femoral excision to 0.51 ؎ 0.10 three weeks after the surgery in the mice treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 32 publications
3
92
1
2
Order By: Relevance
“…Statins are competitive inhibitors of 3-hydroxy-2-methylglutaryl coenzyme A (HMG-CoA) reductase, and are widely used to lower cholesterol levels, which is an important factor in the treatment of hyperlipidemia and arteriosclerosis 4) . Recently, another in vivo effect of statins has also attracted attention, with a number of studies finding that statins promote the differentiation of osteoblasts produced by stimulation with bone morphogenetic protein-2 (BMP-2), indicating their potential in the development of new osteogenic drugs [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Statins are competitive inhibitors of 3-hydroxy-2-methylglutaryl coenzyme A (HMG-CoA) reductase, and are widely used to lower cholesterol levels, which is an important factor in the treatment of hyperlipidemia and arteriosclerosis 4) . Recently, another in vivo effect of statins has also attracted attention, with a number of studies finding that statins promote the differentiation of osteoblasts produced by stimulation with bone morphogenetic protein-2 (BMP-2), indicating their potential in the development of new osteogenic drugs [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment of endothelial progenitor cells with statins, eNOSoverexpression of PPAR-gamma agonists before transfer increases their migratory, invasive, and neovascularization capacity -effects that are mediated by activation of endothelial nitric oxide synthase (Shao et al 2008;Spyridopoulos et al 2004). Similary, own results showed that prestimulation of endothelial progenitor cells from diabetic individuals with the peroxisome proliferator activated receptor -agonist rosiglitazone, enhances nitric oxide availability and the in vivo endothelial repair capacity of these cells (Sorrentino et al 2007).…”
Section: Future Directions Of Cell Based-therapy For Ischemic Heart Dmentioning
confidence: 92%
“…[4][5][6] Statins have also been reported to enhance EPC migration, augment EPC chemotaxis and inhibit EPC apoptosis both in vitro and in vivo. 4,9,10 SDF-1, an 89-amino acid polypeptide, is a member of the chemokine CXC subfamily originally isolated from murine bone marrow stromal cells. 11 SDF-1 was initially identified as a potent chemoattractant for lymphocytes and monocytes, and as an enhancer of B cell proliferation.…”
Section: Angiogenesis Requires the Mobilization Of Progenitor Cells Fmentioning
confidence: 99%
“…16,17 Furthermore, SDF-1 also reduces EPC apoptosis and enhances survival of the progenitor cells. 3,18 SDF-1, either delivered locally in its protein form, 3,19,20 or generated in situ via plasmid and viral vector-mediated gene expression, 10,21,22 enhances neovascularization by augmenting EPC recruitment into ischemic tissues. The potential of statin and stromal cell-derived factor-1 to promote angiogenesis SDF-1 binding to its receptor CXCR4 on the cell surface provides essential signals for mobilization and homing of EPCs to the injured site.…”
Section: Angiogenesis Requires the Mobilization Of Progenitor Cells Fmentioning
confidence: 99%
See 1 more Smart Citation